A STUDY OF LINGUISTIC FEATURES OF PROVERBS CONTAINING WEATHER TERMS IN ENGLISH VERSUS VIETNAMESE - Ph. D HỒ THỊ KIỀU OANH (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
The study is aimed at: • Finding out the differences and similarities of semantic and syntactic features of proverbs containing weather terms in English Vs. Vietnamese. • Helping Vietnamese learners of English and English learners of Vietnamese as a foreign language not only get a better insight into various cultural aspects of the English people and Vietnamese people and even those of their own people, but also to some extent see the beauty of language in general and that of proverbs in particular. • Providing Vietnamese learners of English and English learners of Vietnamese with a practical knowledge of the field to enable them to use them effectively.